The Level of Spiritual Intelligence Among Students of Educational Psychology Course at Jerash University in The Light of Some variables (Journal of the College of Education for Women, 2019)
This study aimed to determine the level of spiritual intelligence among students of educational psychology course at the Jerash University. and whether this level of varies depend on the gender of the student as well as the college type. The study sample consisted of (180) male and female students of bachelor students at the University Jerash, in the second semester of academic year2014-2015. The main results of the study were that the level of spiritualIntelligence of Jerash University students was high. More over There were no statistically significant differences at the level of significance (0.05) due to the effect of gender, college type or academic achievement